Theoretical study of the central depression of nuclear charge density distribution by electron scattering - 刘健 褚衍运 任中洲 王再军 (Chinese physics C, 2012)
The charge form factors of elastic electron scattering for isotones with N=20 and N=28 are calculated using the phase-shift analysis method,with corresponding charge density distributions from relativistic mean-field theory.The results show that there are sharp variations at the inner parts of charge distributions with the proton number decreasing.The corresponding charge form factors are divided into two groups because of the unique properties of the s-states wave functions,though the proton numbers change uniformly in two isotonic chains.Meanwhile,the shift regularities of theminima are also discussed,and we give a clear relation between theminima of the charge form factors and the corresponding charge radii.This relation is caused by the diffraction effect of the electron.Under this conclusion,we calculate the charge density distributions and the charge form factors of the A=44 nuclei chain.The results are also useful for studying the central depression in light exotic nuclei.